Influence of Molybdenum Addition on the Structure, Mechanical Properties, and Cutting Performance of AlTiN Coatings - Tao Yang; Jun Yin; Puyou Ying; Changhong Lin; Ping Zhang; Jianbo Wu; Alexander Kovalev; Min Huang; Tianle Wang; Andrei Y. Grigoriev; Dmitri M. Gutsev; Vladimir Levchenko (Lubricants)
Though AlTiN coating has been intensively studied, there is still a need to develop AlTiN coating to meet the growing demand of industrial machining. One effective way to improve the performance of AlTiN coating is by adding alloying elements. In this study, AlTiN and AlTiMo coatings were deposited using multi-arc ion plating to investigate the influence of molybdenum addition on the structure, mechanical properties, and cutting performance of AlTiN coatings. Spherical droplets formed on the surfaces of both coatings, with the AlTiMoN coating exhibiting more surface defects than the AlTiN coating. The grazing incidence X-ray diffraction results revealed the formation of an (Al,Ti)N phase formed in the AlTiN and AlTiMoN coatings. Molybdenum doping in the AlTiMoN coating slightly reduced the grain size. Both coatings exhibited excellent adhesion to the substrate. The hardness (H), elastic moduli (E), H/E, and H3/E2 ratios of the AlTiMoN coating were higher than those of the AlTiN coating. The improvement in the mechanical properties was attributed to grain refinement and solution strengthening. Molybdenum doping improved the tribological properties and cutting performance of the AlTiN coatings, which was ascribed to the formation of MoO3 as a solid lubricant. These results show a path to increase the performance of AlTiN coating through molybdenum addition and provide ideas for the application of AlTiMoN coatings for cutting tools.